2023
DOI: 10.26668/businessreview/2023.v8i2.1539
|View full text |Cite
|
Sign up to set email alerts
|

Supervisors’ Roles in Training Program Culture, Training Intrinsic Motivation and Knowledge Transfer: an Empirical Study

Abstract: Purpose:  This study examines the mediating role of training intrinsic motivation in the relationship between supervisors’ roles in training program culture and knowledge transfer in the Malaysian public sector. Thus, the research question is, “what is the effect of the supervisors’ roles in training program culture, training intrinsic motivation on knowledge transfer in the public sector context?”   Theoretical framework:  The framework of the study is adopted from the attributes of (1) leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Furthermore, the study confirmed a positive effect of motivation to learn on knowledge transfer. These results are in line with previous literature (Easterby-Smith et al, 2008;Martín Cruz et al, 2009;Gegenfurtner and Vauras, 2012;Zafar et al, 2014;Tho, 2017;Kang and Kim, 2017;Mohamad and Abd Rahman, 2023;Sharif et al, 2023). These results demonstrate that the positive impact of motivation to learn on The results suggest that the indirect pathways play a role in facilitating the drive to learn by establishing a connection between intrinsic motivation and the transfer of knowledge.…”
Section: Measurment Modelsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the study confirmed a positive effect of motivation to learn on knowledge transfer. These results are in line with previous literature (Easterby-Smith et al, 2008;Martín Cruz et al, 2009;Gegenfurtner and Vauras, 2012;Zafar et al, 2014;Tho, 2017;Kang and Kim, 2017;Mohamad and Abd Rahman, 2023;Sharif et al, 2023). These results demonstrate that the positive impact of motivation to learn on The results suggest that the indirect pathways play a role in facilitating the drive to learn by establishing a connection between intrinsic motivation and the transfer of knowledge.…”
Section: Measurment Modelsupporting
confidence: 92%
“…Researchers such as Easterby-Smith et al (2008) and Gegenfurtner and Vauras (2012) also recognize the influential impact of learning motivation on information transmission. Mohamad and Abd Rahman (2023) underscore the significant significance that information transmission plays in facilitating intellectual exchange. The research conducted by Kalling (2003) supports the concept of internal knowledge transmission inside organizations, emphasizing the significant impact of motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourthly, encouraging interaction between leaders and employees is essential because extensive learning is seen as a sociocultural experience that requires social interaction for effective professional development [12]. This approach is particularly crucial in the context of human relationships, selfawareness, problem-solving and decision-making, motivation, values, and effective program management in training [13], [14].Leadership practices in training programs typically employ two task styles: intangible support and tangible support [15], [16]. In training perspective, leadership practice refers to the leader that provides both intangible support (moral or emotional support) and tangible support (material or instrumental support) to trainees in guiding and improving their capabilities before, during, and after the training program [9], [15], [17].…”
Section: Introductionmentioning
confidence: 99%